'We are this hybrid': Members' search for organizational identity in an institutionalized public–private partnership. (14th June 2017) - Reissner, Stefanie C.
Abstract : There has been significant scholarly interest in organizational hybridity, the combination of multiple institutional logics in one entity. However, the extant research has mainly studied the implications for organizations and individuals, neglecting the challenges for organizational members as a collective. To mitigate, this article examines how members of a British institutionalized public–private partnership grapple with the question of what their organization may be, highlighting the confusion they are experiencing and their attempts to overcome it. Drawing on the concept of organizational identity (theorized as the outcome of collective sensemaking), the analysis identifies two mechanisms that recursively connect the organization and its members. Relational positioning draws on possible configurations of institutional logics and associated identity resources while discursive framing captures members' hopes and expectations. The main contribution of this article is a better understanding of collective sensemaking in hybrid organizations in the light of institutional complexity.